Relationship between leg length discrepancy and functional scoliosis in children and adolescents - Fanhui Xi; Xuhong Xue; Enze Ji; Qi Zhang; Sheng Zhao; Kai Li; Yuanwei Li (BMC Musculoskeletal Disorders)
Abstract Purpose As the relationship between leg-length discrepancy (LLD) and scoliosis has not been clearly defined, the purpose of this study was to explore the impact and severity of LLD in children and adolescents with scoliosis and the consistency between lower limb length discrepancy and pelvic height difference. Methods This retrospective study was conducted using prospectively collected data from 63 patients with functional scoliosis-associated LLD who received treatment at our hospital from March 2021 to July 2024. The inclusion criteria included: ①Children or adolescents with functional scoliosis complicated with LLD; ②Scoliosis classified as thoracolumbar or lumbar curve; ③A bilateral acetabular dome line parallel to the superior sacral endplate. The patients’ whole-spine posteroanterior and full lower limb radiographs were obtained to collect data on age, sex, LLD, Cobb angle, and pelvic height difference. Correlation analysis evaluated the relationship between LLD, leg-length discrepancy ratio (LLDR), Cobb angle, and the pelvic height difference. Univariate regression analysis was used to analyze the data using the SPSS software. Results In all cases, the convex side of the scoliosis corresponded to the shorter leg side. Female patients constituted 67% of the cohort. The patients’ mean age was 11.79 ± 3.52 years (range: 4 to 19 years). The average Cobb angle was 14.78 ± 4.99°, the average LLD was 11.22 ± 12.74 mm, and the mean pelvic height difference was 12.41 ± 10.32 mm. Significant correlations were observed when the bilateral acetabular dome line was parallel to the superior sacral endplate, and the scoliosis was thoracolumbar or lumbar, indicating associations between LLD and the Cobb angle (R = 0.440, P<0.05) and between LLDR and the Cobb angle (R = 0.445, P<0.05). Additionally, a strong positive correlation was identified between LLD and pelvic height difference (R = 0.874, P<0.05), indicating a high level of concordance between pelvic height difference and LLD. Conclusions In children and adolescents with functional scoliosis complicated by LLD, the Cobb angle significantly correlated with LLD. Additionally, LLDR also showed a significant correlation with the Cobb angle. A concordance was also observed between the pelvic height difference and LLD. Clinical trial number Not applicable.